INOVASI DAN TREN PAKET WISATA ERA DIGITAL 5.0 DI KABUPATEN BELU NUSA TENGGARA TIMUR - Linda Marlince Taka; Habel Ada Koinmanas (PARIWISATA BUDAYA: JURNAL ILMIAH PARIWISATA AGAMA DAN BUDAYA, 2025)
This research aims to identify and analyze the innovations and trends of tour packages developing in Belu Regency in facing the 5.0 era, an era where digital technology and artificial intelligence are increasingly affecting various sectors, including tourism. Belu Regency, located in East Nusa Tenggara, has great tourism potential, but still faces challenges in developing tour packages that suit the needs and preferences of modern tourists. Through a qualitative approach, this research collected data through interviews with tourism industry players, as well as literature studies related to technological innovation in the tourism sector. The results show that in the 5.0 era, Belu Regency has begun to integrate technology such as mobile applications, online booking systems, and social media in the development of tour packages. Emerging trends include local experience-based tour packages, culture- and nature-based tourism, and the use of technology to provide more personalized and interactive services for tourists. However, there are still constraints related to digital infrastructure and human resource capacity in managing these technologies. This research recommends the importance of collaboration between the government, local communities, and the private sector in accelerating the adoption of innovations to improve Belu Regency's tourism competitiveness in the digital era.